Measurements of nocturnal radiation made at Dum Dum airport, Calcutta (MAUSAM, 1964)
A report on the measurements of net outgoing long wave radiation (nocturnal radiation) and incoming long wave radiation (sky radiation} made at Dum Dum airport, Calcutta, with an Angstrom Pyrgeometer for the period November 1959 to March 1962 has been presented, Values of monthly net outgoing nocturnal radiation and sky radiation expressed -as percentage of black body radiation for clear sky nights have been presented in a tabular form. An empirical relation of the effect of cloud on the net outgoing radiation has been suggested, The effect of haze/dust particles on the net outgoing radiation has also been discussed.